Concepts and implementation of PID controllers in a smelting furnace steel - Jiménez-Ceciliano, Pablo Javier (2014)
The importance in the industry of having accurately controlled process to avoid that they run out of their specific operating point, has led to develop different control systems, the following article describes one of many systems, the PID drivers (Proportional, Integral, Derivative). The importance in the industry of having accurately controlled process to avoid that they run out of their specific operating point, has led to develop different control systems, the following article describes one of many systems, the PID drivers (Proportional, Integral, Derivative). These drivers are in charge to maintain a process in on stable state of work, when there are controlled or random variations of the system by a transfer function, the tuning parameters of the driver are in charge to bring back the system at its respective operating point. Moreover, different graphics generated by the SIMULINK tool of MATLAB will be analyzed to facilitate the concepts comprehension and in this study, the identification and tuning are also on important part of it.